Evidence Rules In Disputes Related To The Nationality Law - جامع شادي; ميهوب أحمد (Latakia University Journal - Economic and Legal Sciences Series, 2021)
The importance of proof of nationality derives from the importance of nationality itself and in terms of it being the adaptation of the individual’s life in the state and in the international community. The individual’s need to prove his nationality is related to his daily life as much of his rights, obligations, actions, and relations with others depend on it. The importance of proving nationality does not seem necessary only when a judicial dispute over a person’s nationality arises, but it also takes place outside the framework of the judicial dispute and in every case in which it is necessary to prove the person’s nationality status, whether to defend his interests or confront others or to determine his treatment in terms of rights and obligations With regard to the various authorities and authorities in the concerned countries or before other countries.